Effect of diversity management on organizational trust, employee innovative behavior, and employee engagement: Evidence from Indonesia - Anastasia M. D. Batmomolin; Muhammad Sadikin; Jimmy S. Hadi; Andreas Wahyu Gunawan P.; Stefanus M. S. Sadana (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2022)
Internationalization and economic globalization cause diversity in organizations to be higher, thus requiring a diversity management approach. This quantitative study aims to analyze the effect of diversity management on organizational trust, employee innovative behavior, and employee engagement. Data were collected using a questionnaire involving 115 employees of a large private bank in Jakarta, Indonesia. Analysis of research data using structural equation modeling (SEM) with SmartPLS software. The results showed that diversity management has a positive effect on organizational trust, employee innovative behavior, and employee engagement. Organizational trust has a positive effect on employee innovative behavior and employee engagement. Organizational trust mediates the effect of diversity management on employee innovative behavior and employee engagement. Diversity management is very important for organizations today because it can promote organizational trust, create employee innovative behavior and strengthen employee engagement, so every organization needs to establish policies regarding diversity management practices and consistently make it happen.
Keywords: M14; O15; 330; Diversity management; Organizational trust; Employee innovative behavior; Employee Engagement; Indonesia